2008
DOI: 10.1111/j.1365-294x.2008.03706.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of vicariance vs. dispersal in shaping genetic patterns in ocellated lizard species in the western Mediterranean

Abstract: The schism between North Africa and Southern Europe caused by the opening of the Strait of Gibraltar and the consequent refilling of the Mediterranean basin at the end of Messinian salinity crisis (MSC), 5.33 million years ago, has been advocated as the main event shaping biogeographical patterns in the western Mediterranean as exemplified by the distribution of species and subspecies and genetic variation within the ocellated lizard group. To reassess the role of the MSC, partial sequences of three mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
112
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(121 citation statements)
references
References 49 publications
7
112
1
1
Order By: Relevance
“…In general, the differentiation pattern found for Iberian and North African pond turtles mirrors a common paradigm for North African amphibians and reptiles, with Moroccan populations often being well-differentiated from their eastern Algerian and Tunisian counterparts (e.g., Pleurodeles spp., Veith et al 2004; Hyla meridionalis, Recuero et al 2007;Mauremys leprosa, Fritz et al 2006b;Testudo graeca, Fritz et al 2009b; Chamaeleo chamaeleon, Dimaki et al 2008; Timon spp., Paulo et al 2008;Coronella girondica, Santos et al 2012; Macroprotodon spp., ; Malpolon spp., Carranza et al 2006; Natrix maura, Guicking et al 2008; Vipera latastei complex, Velo-Antón et al 2012), while Moroccan and Iberian populations can be often very similar (e.g., Pleurodeles waltl, Veith et al 2004;Mauremys leprosa, Fritz et al 2006b;Testudo graeca, Fritz et al 2009b;Graciá et al 2013;Macroprotodon brevis, Carranza et al 2004;Malpolon monspessulanus, Carranza et al 2006). This suggests that the Straits of Gibraltar constitutes no significant biogeographic barrier for these taxa, and this may be especially true for E. orbicularis, as indicated by the weak differentiation of pond turtles from southern Spain (Doñana National Park) and Morocco (Fig.…”
Section: Biogeographymentioning
confidence: 99%
“…In general, the differentiation pattern found for Iberian and North African pond turtles mirrors a common paradigm for North African amphibians and reptiles, with Moroccan populations often being well-differentiated from their eastern Algerian and Tunisian counterparts (e.g., Pleurodeles spp., Veith et al 2004; Hyla meridionalis, Recuero et al 2007;Mauremys leprosa, Fritz et al 2006b;Testudo graeca, Fritz et al 2009b; Chamaeleo chamaeleon, Dimaki et al 2008; Timon spp., Paulo et al 2008;Coronella girondica, Santos et al 2012; Macroprotodon spp., ; Malpolon spp., Carranza et al 2006; Natrix maura, Guicking et al 2008; Vipera latastei complex, Velo-Antón et al 2012), while Moroccan and Iberian populations can be often very similar (e.g., Pleurodeles waltl, Veith et al 2004;Mauremys leprosa, Fritz et al 2006b;Testudo graeca, Fritz et al 2009b;Graciá et al 2013;Macroprotodon brevis, Carranza et al 2004;Malpolon monspessulanus, Carranza et al 2006). This suggests that the Straits of Gibraltar constitutes no significant biogeographic barrier for these taxa, and this may be especially true for E. orbicularis, as indicated by the weak differentiation of pond turtles from southern Spain (Doñana National Park) and Morocco (Fig.…”
Section: Biogeographymentioning
confidence: 99%
“…Other workers (ARANO et al, 1998;CARRANZA & WADE, 2004;FROMHAGE et al, 2004;MARTÍNEZ-SOLANO et al, 2004;VEITH et al, 2004) have also discovered genetic discontinuities of the same order of magnitude. BARBADILLO et al (1997), and later CARRANZA & WADE (2004) and PAULO et al (2008), presented very convincing hypotheses based on fragmentation of basal populations, before and during the Messinian Crisis, to explain discontinuities. These authors suggested that the area now comprising the coast of northwestern Africa and the southern Iberian Peninsula once belonged to a series of islands belonging to a geologic complex named Alkapeca (MICHARD et al, 2002).…”
Section: The Tellmentioning
confidence: 99%
“…The same individual carries also an European allele at the melanocortin-1 receptor gene (JF732954, Nunes et al, 2011b). Although technical errors cannot be entirely ruled out, the cytochrome b haplotype obtained for this individual undoubtedly belongs to the North African clade (AF378959, Paulo et al, 2008), and it clusters with Moroccan samples based on neutral microsatellites (Paulo, unpublished data). Given the long time (about 11 million years) of divergence and isolation of this species from European lizards , it is unexpected to find such a level of ancestral polymorphism retained in a single individual at the nuclear level.…”
Section: Outlier Sequence Variation In Ocellated Lizardsmentioning
confidence: 99%
“…The species is widespread throughout the Iberian Peninsula in a variety of ecological conditions that are strongly influenced by the distribution of precipitation and temperature ranges. Morphological and genetic differentiation in populations from the northwest and southeast of the Iberian Peninsula are strong enough to consider those populations as distinct subspecies: Lepida lepida iberica and Lepida lepida nevadensis, respectively (Mateo and Castroviejo, 1990;Paulo et al, 2008). The first lives in a rainy and lesswarm weather regime, whereas the second inhabits a region that experiences hot summers and the lowest annual rainfall across the species' distribution range.…”
Section: Introductionmentioning
confidence: 99%